2018
DOI: 10.1098/rsos.181065
|View full text |Cite
|
Sign up to set email alerts
|

Environmental oestrogens cause predation-induced population decline in a freshwater fish

Abstract: Understanding population-level effects of environmental stressors on aquatic biota requires knowledge of the direct adverse effects of pollutants on individuals and species interactions that relate to survival and reproduction. Here, we connect behavioural assays with survival trials and a modelling approach to quantify changes in antipredator escape performance of a larval freshwater fish following exposure to an environmental oestrogen, and predict changes in population abundance. We quantified the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 82 publications
1
16
0
Order By: Relevance
“…Increased predation mortality following exposure to environmental contaminants has been reported in a number of aquatic species ( Weis et al. 2001 ), including P. promelas ; for example, Rearick et al. (2018) showed that the survival of larvae exposed to low or high concentrations of 17β-estradiol was reduced by 10% and 11%, respectively, in predation trials involving sunfish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased predation mortality following exposure to environmental contaminants has been reported in a number of aquatic species ( Weis et al. 2001 ), including P. promelas ; for example, Rearick et al. (2018) showed that the survival of larvae exposed to low or high concentrations of 17β-estradiol was reduced by 10% and 11%, respectively, in predation trials involving sunfish.…”
Section: Discussionmentioning
confidence: 99%
“…2009 ; Ward et al. 2017 ) suggesting that it has the potential to alter predator–prey dynamics ( Rearick et al. 2018 ); however, whether such changes translate into higher predation rates and how E1 affects predator efficacy is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In fish, water-borne estrogenic pollutants have wide-ranging behavioral and physiological effects. Effects include alterations to behaviors that are also affected by nociceptive plasticity, such as aggression, anxiety and responses to predators (Dang et al, 2017;Dzieweczynski et al, 2014;Rearick et al, 2018;Volkova et al, 2015); however, whether similarly complex effects occur in aquatic invertebrates is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are likely to extend to invertebrates such as cephalopods, which are important components of inshore food webs as eggs laid in the nearshore benthos, and juvenile and adult stages inhabiting shallow coastal waters. Injured and compromised prey represent preferred targets for many predatory species (Bowerman et al, 2010;Crook et al, 2014;Krumm et al, 2010;Semlitsch, 1990), and there is evidence that predation rates are affected by estrogen exposure in some fish species (Rearick et al, 2018); thus, any disruption to behavioral and neural plasticity processes that underlie adaptive responses to injury may have wide-ranging effects on marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, impairments to swimming and foraging behaviors for fry of Lake Trout Salvelinus namaycush suffering from thiamine deficiency led to increased starvation and, when coupled with a high predation rate, resulted in a collapse of a simulated cohort (Ivan et al 2018). Furthermore, larval Fathead Minnows exposed to 17β‐estradiol exhibited reduced antipredator escape performance, and the resulting higher predation mortality rate led to a simulated population decline (Rearick et al 2018). Therefore, it is important that fishery managers consider the sublethal effects of contaminants when assessing wild fish populations.…”
mentioning
confidence: 99%